Microglial depletion and repopulation differentially modulate sleep and inflammation in a mouse model of traumatic brain injury - Katherine R. Giordano; Tabitha R.F. Green; Mark R. Opp; Rachel K. Rowe (Neurobiology of Sleep and Circadian Rhythms)
Traumatic brain injury (TBI) causes persistent sleep disturbances, leading to long-term neurological consequences and reduced quality of life. We hypothesized that microglial depletion via PLX5622 (PLX), a colony-stimulating factor 1 receptor (CSFR1R) inhibitor, would exacerbate sleep disturbances and alter inflammatory profiles after TBI, and that microglial repopulation would ameliorate these effects. Male mice received PLX or control diets (21 days) followed by a midline fluid percussion injury (mFPI) or sham surgery. Physiological parameters were recorded non-invasively to determine sleep for 7 days post-injury. Subsequently, PLX was withdrawn to allow microglial repopulation, and sleep was assessed during the 7-day repopulation period. In a subset of mice, repeated blood draws were taken to quantify sleep regulatory cytokine concentrations (interleukin [IL]-6, IL-1β, tumor necrosis factor [TNF]-α). TBI significantly reduced sleep in mice on a control diet during the light period (3, 5, and 7 days post-injury), but not the dark period. In PLX-treated mice, TBI did not alter sleep in the light period, however, sleep in the dark period was increased at 3 days post-injury. During the microglial repopulation period, PLX-treated TBI mice slept significantly more in the dark period compared to PLX sham mice and sleep was similar in control TBI vs PLX TBI mice. Analyses revealed that elimination of microglia did not alter baseline cytokine levels. IL-6 was elevated in PLX TBI mice at 1 and 7 days post-injury compared to TBI mice on control diet, while IL-1β and TNF-α remained unchanged. This study highlights the critical role of microglia in modulating post-TBI sleep and inflammation. Findings suggest differential effects of TBI on sleep depending on microglial depletion or repopulation status, with IL-6 serving as a marker of the inflammatory response in microglia-depleted conditions.